THE ROLE OF WADIAH DEMAND DEPOSITS AND OPERATING INCOME ON THE NET INCOME PERFORMANCE OF SHARIA CENTRAL ASIA BANK (BCA) - Khairisma; Mutia Dara Fonna; Yoesrizal Muhammad Yoesoef (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2023)
This study looks at how operational revenue and wadiah demand deposits affect Bank Central Asia's (BCA) Syariah's net profit between 2016 and 2021. A total of 72 data points from monthly financial data reports from this time period make up the sample. The analysis uses the data analysis method known as Structural Equation Modeling-Partial Least Squares (SEM-PLS). Examining the connections between wadiah demand deposits, operating income, and net profit at BCA Syariah was the goal of this study. Customers who use wadiah demand deposits entrust their money to the bank for safekeeping as a particular kind of Islamic banking deposit. On the other side, operating income indicates the revenue from BCA Syariah's primary operational activities. The study offers important insights into the relationship between these variables by using SEM-PLS analysis. The findings show that wadiah demand deposits do not considerably affect net profit, proving that changes in these deposits do not significantly affect the profitability of the bank as a whole. But the study shows a statistically significant link between operational income and net profit. This result implies that variations in BCA Syariah's operating income have a direct impact on the company's net profit.